2022
DOI: 10.1038/s41598-022-17432-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol monolaurate inhibition of human B cell activation

Abstract: Glycerol monolaurate (GML) is a naturally occurring antimicrobial agent used commercially in numerous products and food items. GML is also used as a homeopathic agent and is being clinically tested to treat several human diseases. In addition to its anti-microbial function, GML suppresses immune cell proliferation and inhibits primary human T cell activation. GML suppresses T cell activation by altering membrane dynamics and disrupting the formation of protein clusters necessary for intracellular signaling. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… Zhang et al (2016) found that GML treatment drastically altered the lipid phase dynamics in the plasma membrane of human T cells, consequently inhibiting TCR-induced PI3K-AKT signaling axis and calcium influx, and reducing the production of cytokines such as IL-2, IFN-γ, TNF-α, and IL-10. In another study, GML significantly suppressed the production of IL-6 and TNF-α cytokines in BCR-induced human primary B cells ( Fosdick et al, 2022 ). In the present study, our results showed that TLR4, IL-1β and TNF-α mRNA expressions in spleen as well as TLR4 and IL-6 in jejunum decreased linearly with the increase of dietary GML concentration.…”
Section: Discussionmentioning
confidence: 91%
“… Zhang et al (2016) found that GML treatment drastically altered the lipid phase dynamics in the plasma membrane of human T cells, consequently inhibiting TCR-induced PI3K-AKT signaling axis and calcium influx, and reducing the production of cytokines such as IL-2, IFN-γ, TNF-α, and IL-10. In another study, GML significantly suppressed the production of IL-6 and TNF-α cytokines in BCR-induced human primary B cells ( Fosdick et al, 2022 ). In the present study, our results showed that TLR4, IL-1β and TNF-α mRNA expressions in spleen as well as TLR4 and IL-6 in jejunum decreased linearly with the increase of dietary GML concentration.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research has confirmed that GML can inhibit T-cell activation and suppress cytokine production, such as IL-2, interferon ( IFN )-γ, TNF-α, and IL-10, in a dosage-dependent manner ( Zhang et al, 2016 ). Glycerol monolaurate has also been shown to inhibit B cell receptor-induced cytokine production, phosphorylation of signaling proteins, and protein clustering ( Fosdick et al, 2022 ). Moreover, oral administration of GML inhibits the infiltration of macrophages and reduces the expression of proinflammatory factors, thereby contributing to the alleviation of experimental colitis in mice ( He et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%